Pemikiran Ibnu Sina Tentang Pendidikan dan Relevansinya di Era Society 5.0 - Wanto, Eko Kurnia; Khojir, Khojir (Journal of Islamic Education Policy, 2023)
The purpose of this reseach is to find out how Ibn Sina thinks about education and its relevance in the era or society 5.0. in order to encourage the development or Islamic religious education, efforts are needed to research and expand the scientific knowledge of Ibn Sina?s thought of Islamic education, for the sake of scientific wealth and the benefits of knowledge both among educational institutions and the wider community, more specifically Muslim increase their understanding of Ibn Sina?s thoughts in education, so that Muslim to understand and understand more deeply. This type of research is literature and the method used in this research uses the documentation method (data collection), which tries to present or present data and information in depth and intact, then analyses it with the approach of Islamic philosophy as the analysis knife, then we take the opinions or educational experts, then we take the opinions or educational expert. The results of this study indicate that Ibnu Sina?s thoughts about education are compatible with other educational experts and there is relevance in the era of society 5.0, that human education must mobilize all human potential (human beings) including experts in technology who do not inly emphasize business. Of course, but with the technology of the era of society 5.0, a new value is created that will eliminate social, age, gender, language specifically desgned for various individual needs and the needs of many people.